Prospects of the vacuum aspiration biopsy in terms of making the diagnoosis of malignant neoplasms of the mammary glands in patients categorised 3 and 4 according to BIRADS scale - S. S. Skurikhin; I. A. Bolotin; O. L. Chagunava; A. B. Guslev (Исследования и практика в медицине, 2022)
Purpose of the study. Was to assess the prospects for the use of vacuum aspiration biopsy in terms of breast cancer diagnosis in patients with focal breast changes categorised by 3 and 4a according to the BIRADS scale.Materials and methods. In the period from February 2020 to July 2021, 41 (n = 41) the patient with nodules of 3 and 4a categories according to BIRADS has been passed 41 vacuum aspiration biopsies (VAB) (n = 41) under local infiltration anesthesia with ultrasound navigation. The 17 % (n = 7) of the nodular neoplasms were represented by multiple lesions. The ultrasound examination was mandatory for all the patients and the 17 % (n = 7) was combined with mammography. Invasive diagnostics of tissue material from tumors subject to VAB was previously performed in 5 patients. Trephine biopsy was also performed in 4 cases and the fine needle aspiration biopsy (TAB) was performed in 1 case. Tissue atypia was not detected in all cases.Results. The removed lesions were benign in 85.3 % (n = 35) of the cases. Breast cancer was diagnosed in 4.8 % of cases (n = 2), cancer in situ was diagnosed in 9.7 % (n = 4). The cases of invasive cancer were observed in both BIRADS categories, while in situ cancer was diagnosed in only 4a BIRADS categories. The residual tissue of the formation was detected in 1 case (n = 1). During the procedure, no complications were revealed. Moreover, in the early postoperative period, seroma formation has occurred in 2 patients 4.8 % (n = 2). All the patients noted the satisfactory tolerance to the manipulation.Conclusion. The data obtained suggest that vacuum aspiration biopsy has a high diagnostic accuracy and certain advantages in this category of patients, in particular cases of urgent need to conduct more precise invasive diagnostics without performing the excisional biopsy examination.